Kontekstualność w nauczaniu literatury - Zaborowska, Wiesława (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
This article contains a review of contexts used in school-didactics of literature. The definition of intertextuality, context and other theoretical problems are considered in the first chapter. Second chapter contains a review of each kind of contexts. At the beginning the author describes the literary contexts related to the analyzed by the means of allusion. He also writes about Bible and mythology. The following part consists of a review of auxiliary contexts, which belong to other sciences: history of literature, history, philosophy, ethics, psychology,’ sociology and geography. The next part covers the texts of culture: aesthetics, theatre, film, music, painting, sculpture, architecture and museum-exhibitions. The last chapter contains suggestions of how to use contexts during Polish language lessons: their place teaching programs as well as presence on various educational stages. The final part of this work contains a description of problems and advantages connected to the usage of contexts in literature didactics.